2013
DOI: 10.5897/ajb2013.12125
|View full text |Cite
|
Sign up to set email alerts
|

A thirteen week ad libitum administration toxicity study of Tartrazine in Swiss mice

Abstract: Tartrazine is a colorant widely used in food products, drugs and cosmetics. The current study evaluates the effect of sub-chronic ingestion of tartrazine in drinking water at doses of 0, 0.1, 0.45, 1 and 2.5% for 13 weeks in mice. Our results show that female body weight gain and food consumption decreased in all treated groups, while fluid consumption increased. The red blood cell count, hemoglobin and hematocrit were increased in male 2.5% treated groups and the white blood cell count decreased in all treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In addition, these results are in agreement with data reported by Amin, Abdel Hameid & AbdElsttar (2010) who revealed a significant increase in serum creatinine and urea levels in rats after consumption of tartrazine. Recently, Nabila et al (2013) mentioned that tartrazine application induced significant elevations in urea and creatinine levels that is associated with impaired renal function and the inability of the kidney to filter body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these results are in agreement with data reported by Amin, Abdel Hameid & AbdElsttar (2010) who revealed a significant increase in serum creatinine and urea levels in rats after consumption of tartrazine. Recently, Nabila et al (2013) mentioned that tartrazine application induced significant elevations in urea and creatinine levels that is associated with impaired renal function and the inability of the kidney to filter body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Sasaki et al using a comet assay, tartrazine that was applied at a dose of 7.5 mg/kg could induce DNA damage in the colon of mice [22]. Nabila Mehedi et al concluded that tartrazine applied in drinking water at the different low doses induced depression of body weight and adverse effects on the organs of Swiss mice [31]. Moreover, lesions in the brain, liver, and kidneys in animals treated with tartrazine were observed.…”
Section: Discussionmentioning
confidence: 81%
“…In the study realized by Mehedi et al [31] was demonstrated that sub-chronic ingestion of tartrazine at low doses added in water could cause a structural alteration of the spleen and intestine, inducing a depressing effect on the humoral immune response in male mice. According to recent findings [28,32] tartrazine is able to generate ROS (reactive oxygen species), accelerating oxidative stress, modifying the biochemical profiles and structure in the renal and hepatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these results are in agreement with data reported by Amin et al (2010) who revealed a significant increase in serum creatinine and urea levels in rats after consumtion of tartrazine. Recently, Nabila et al(2013) mentioned that tartrazine application induced significant elevations in urea and creatinine levels that is associalted with impared renal function and the inability of the kidney to filter body fluids.…”
Section: Discussionmentioning
confidence: 99%